2016
DOI: 10.1177/1533034616661447
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Dose to Pelvic Nodal Regions in Prostate-Only Radiotherapy

Abstract: Objectives: Pelvic lymph nodal regions receive an incidental dose from conformal treatment of the prostate. This study was conducted to investigate the doses received by the different pelvic nodal regions with varying techniques used for prostate radiotherapy. Methods and Materials: Twenty patients of high-risk node-negative prostate cancer treated with intensitymodulated radiotherapy to the prostate alone were studied. Replanning was done for intensity-modulated radiotherapy, 3-dimensional conformal treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our results support previous observations that incidental dose outside the target region is associated with reduced BCR in high-risk prostate cancer patients (18,24,45), providing further evidence for adapting the treatment volume for men with high-risk disease. Further, the regions observed in both IBDM methods do cover part of the obturator region and external iliac nodes, supporting previous observations (18) and PSMA-PET studies (26) providing further evidence of nodal disease and for inclusion of nearby lymph nodes in the treatment volume for men with high-risk disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results support previous observations that incidental dose outside the target region is associated with reduced BCR in high-risk prostate cancer patients (18,24,45), providing further evidence for adapting the treatment volume for men with high-risk disease. Further, the regions observed in both IBDM methods do cover part of the obturator region and external iliac nodes, supporting previous observations (18) and PSMA-PET studies (26) providing further evidence of nodal disease and for inclusion of nearby lymph nodes in the treatment volume for men with high-risk disease.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, whilst radiotherapy techniques try to limit dose outside of the Planning Target Volume (PTV) to spare normal tissues, studies have shown that incidental dose outside of the PTV could be inadvertently treating subclinical disease (23). Witte et al (18) and Chen et al (24) used Image Based Data Mining technique (IBDM), where the local association between dose and outcome is explored on a per-voxel basis, and found that that incidental dose to the obturator was associated with improved outcomes (25), a region that had previously been associated with clinically relevant incidental dose (26). More recently, Witte et al suggested that the relationship between incidental dose and BCR is influenced by fractionation when they identified a region in the in obturator internus muscles where incidental dose was beneficial for patients treated with standard fractionation radiotherapy, but not in patients treated with a hypo-fractionated schedule (27).…”
Section: Introductionmentioning
confidence: 99%
“… 20 The largest benefit was observed in the obturator area close to the prostate where the mean dose was lowered from 44 Gy to 29 Gy and 22 Gy when switching from 2D EBRT to 3D conformal radiotherapy and IMRT, respectively. 20 …”
Section: Discussionmentioning
confidence: 95%
“…This is in line with the results reported in the study by Murthy et al, who also clearly showed that modern radiotherapy techniques reduce the incidental dose to the pelvic areas in the vicinity of the prostate due to steeper dose gradients. 20 The largest benefit was observed in the obturator area close to the prostate where the mean dose was lowered from 44 Gy to 29 Gy and 22 Gy when switching from 2D EBRT to 3D conformal radiotherapy and IMRT, respectively. 20 Recently, the benefit of applying WPRT in PCa patients with a high risk of pelvic LN involvement, defined as a risk of >20% based on the Roach formula, was shown in a randomized trial.…”
Section: Discussionmentioning
confidence: 95%